Trauma-Informed Spiritual Care: Interventions for Safety, Meaning, Reconnection, and Justice. Fortress Press, 2024. By Danielle Tumminio Hansen. 128 pp. - Lee, Wonjong H. (Pastoral psychology, 2025)
This book review explores Trauma-Informed Spiritual Care by Danielle Tumminio Hansen, which bridges the gap between spirituality and psychology in trauma care. Tumminio Hansen integrates Judith Herman’s three-stage trauma recovery model with spiritual perspectives and restorative justice approaches. The book addresses trauma’s multifaceted nature, emphasizing its individual and collective impacts. It guides spiritual caregivers through creating safety, facilitating meaning-making, and promoting reconnection for trauma survivors. Tumminio Hansen’s work provides practical tools for spiritual care practitioners, balancing theoretical frameworks with real-world applications. The review highlights the book’s strengths in offering a comprehensive methodology for trauma-informed spiritual care, while suggesting areas for further exploration, particularly in differentiating spiritual safety from physical and psychological safety. Overall, the book is recommended as a valuable resource for those in spiritual care, pastoral counseling, or chaplaincy roles.